Empowerment and Assistance of Mosque Functions through the SMART Mosque Model for Mosque Management Boards in Mandailing Natal Regency - Ricka handayani; Ega Putri Duana Manalu; Magdalena Magdalena; Hasbi Anshori; M.Anjas Wa’dah Lubis (CV. AFDIFAL MAJU BERKAH, 2026)
This community service activity aims to increase the understanding and capacity of the management of the Mosque Conservation Agency (BKM) in Mandailing Natal Regency regarding the optimization of mosque functions through the Smart Mosque concept. This program was carried out in the form of providing materials and assistance to 30 participants who were BKM administrators from several local mosques. The material presented focused on strengthening the role of mosques as a center of worship, education, social, and empowerment of the people with the support of digital technology. The method of implementing the activity includes the delivery of materials, interactive discussions, and question and answer sessions to explore the understanding and needs of participants related to the application of the Smart Mosque concept. The results of the activity showed that the participants gained increased knowledge about the function and strategic role of mosques in the digital era. In addition, participants showed high enthusiasm in planning the application of simple technologies, such as the use of social media and digital-based information systems, to support religious activities and mosque administration. This activity has a positive impact in strengthening the institutional capacity of mosques towards more modern, transparent, and service-oriented management.